Relationship between stunting with dental and oral status in toddlers - Munifah Abdat; Said Usman; Hafidha Suhaila; Chairunas (Journal of Dentomaxillofacial Science, 2020)
Objective: To find out the relation between stunting and the dental and oral status of toddlers.Materials and Methods: An analytic observational study with a cross-sectional approach in Pidie district, Aceh. The subject consists of 70 stunting and normal toddlers. The method used is by measure the deft index and OHIS (Oral Hygiene Index Simplified) in toddlers, and also giving questionnaires patterns of dental and oral health behavior. Processing of research data using SPSS 24.0 with Pearson Correlation test and Kendall tau test, also significant value p<0.05.Results: Based on questionnaire results, many parents of stunted no attention to his oral hygiene of their toddlers. The results ofÂ measurements with deft index in stunting and normal toddlers show stunting toddlers at 6.13 (very high category) and normal toddlers 3.7 (Moderate category). Analytic with Pearson correlation test between nutritional status (stunting and normal) and deft results were 0.023<0.05 and OHIS were 0.010<0.05. Kendallâ€™s tau test results showed a value of 0.020<0.05. There is a relationship between nutritional status variables with deft and there is a relationship between nutritional status variables and OHIS.Conclusion: There was a significant relationship between stunting with the dental and oral status in toddlers, the strength of the correlation is sufficient.